Investigation of canine chaphamaparvovirus, canine bufavirus, and canine adenovirus in dogs with diarrhea: First report of novel canine bufavirus in Turkey - Abayli, Hasan; Aslan, Oznur; Tumer, Kenan Cagri; Can-Sahna, Kezban; Tonbak, Sukru (Springer, 2023)
Viral enteritis is a significant cause of death among dogs younger than 6 months. In this study, the presence of canine chaphamaparvovirus (CaChPV), canine bufavirus (CBuV), and canine adenovirus (CAdV) was investigated in 62 diarrheal dogs previously tested for other viral pathogens (canine parvovirus type 2, canine coronavirus, and canine circovirus). CBuV was detected in two dogs (3.22%) and CaChPV in one dog (1.61%). One dog tested positive for three parvoviruses (CPV-2b, CBuV, and CaChPV). All dogs tested negative to CAdV-1/CAdV-2. A long genome fragment of one of the two identified CBuVs and of the CaChPV was obtained and analyzed. New Turkish CBuVs had high identity rates (96%-98% nt; 97%-98% aa) with some Italian CBuV strains (CaBuV/9AS/2005/ITA and CaBuV/35/2016/ITA). The phylogenetic analysis powerfully demonstrated that these viruses belonged to a novel genotype (genotype 2). A part of the genome ChPV-TR-2021-19 revealed high identity rates (> 98% nt and > 99% aa) with some Canadian CaChPV strains (NWT-W88 and NWT-W171) and the Italian CaChPV strain Te/37OVUD/2019/IT. This study is the first report on the detection of CBuV-2 and the concomitant presence of three canine parvoviruses in Turkey. The obtained data will contribute to the molecular epidemiology and the role in the etiology of enteric disease of new parvoviruses.
Keywords: Adenovirus; Bufavirus; Carnivore; Chaphamaparvovirus; Dog; Turkey